Inflected Infinitive in the Corpus de textos galegos escritos por estudantes no ámbito académico (CORTEGAL) - Álvarez de la Granja, María (Madrygal. Revista de Estudios Gallegos, 2020)
This paper analyzes the use of the inflected infinitive (II) in the Corpus de textos galegos escritos por estudantes no ámbito académico (CORTEGAL), which contains texts written by students in their last year of secondary education in Galicia. Following a description of the basic traits of this corpus and the methodology employed to identify the examples that use the II, we present the results obtained, both globally and with respect to their distribution according to different criteria (number and person; syntactic role of the infinitive or of the clause it integrates; whether the subject of the II is coreferential with the subject of the main clause; position of the infinitive clause; presence of lexical subject). Thirdly, we analyze the results in comparison with the findings of other works on the use of the II and by assessing the adequacy of the former to the uses established as canonical in Galician grammars. The paper concludes with a summary of the most important findings of the study, among which we should highlight the low use of the II and the errors in the selection of number and person, along with final considerations on the teaching of this verb form.